Detailed structural and topological analysis of SnBi2Te4 single crystal. (March 2023) - Saxena, Ankush; Karn, N.K.; Sharma, M.M.; Awana, V.P.S.
Abstract: We report herein the successful synthesis of the topological material SnBi2 Te4 in single-crystal form. Phase purity and unidirectional growth are evident from X-ray diffraction (XRD) patterns acquired from a powdered sample and a crystal flake. The crystalline morphology has also been visualized by acquiring a field-emission scanning electron microscope (FESEM) image. The crystal has been thoroughly characterized by means of Raman spectroscopy and X-ray photoelectron spectroscopy (XPS) measurements. The topological properties of SnBi2 Te4 have been probed through magneto-transport measurements. SnBi2 Te4 has been found to exhibit a small but non-saturating magneto-resistance (MR) up to ±12 T. The low-field magnetoconductivity (MC) of SnBi2 Te4 at 2 K can be well explained through the Hikami–Larkin–Nagaoka (HLN) formalism, which confirms the presence of a weak anti-localization (WAL) effect in its crystal. Moreover, the non-trivial topological character has been evidenced through first-principles calculations using density functional theory (DFT), with and without spin-orbit coupling (SOC) protocols. A significant change in the bulk electronic band structure is observed upon the inclusion of SOC parameters, signifying topological properties of SnBi2 Te4 . Its topological non-trivial character has also been verified through calculation of Z2 invariants and the surface states spectrum in the (111) plane. Highlights: Successful synthesis of single crystal of topological material, SnBi2 Te4 . X-ray diffraction, Field Emission Scanning Electron Microscope (FESEM) image, Raman X-ray Photoelectron Spectroscopy (XPS). Topological properties of SnBi2 Te4 probed through magneto-transport measurements. SnBi2 Te4 exhibited small but non-saturating magneto-resistance (MR) up to ±12 T. The low field magnetoconductivity (MC) of SnBi2 Te4 at 2 K is found to follow Hikami-Larkin-Nagaoka (HLN) formalism. The non-trivial topological character is evidenced through first principle calculations using Density Functional Theory (DFT) under with and without spin orbit coupling (SOC) protocols. Topological non-trivial character is also verified through calculation of Z2 invariants and surface states spectrum in (111) plane.